2023
DOI: 10.1021/acs.iecr.2c03645
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Catechol-Grafted Quaternized Chitosan Flocculant for Efficiently Treating Suspended Particles and Refractory Soluble Organic Pollutants

Abstract: It remains challenging yet of great importance to develop a qualified biopolymer-derived flocculant in treating complex high-salinity wastewaters polluted by suspended solids and refractory soluble organic substances such as organic dyes. The key to this success is to endow the developed flocculants with versatile intermolecular and interfacial interactions in high salinity to trigger effective flocculation. Herein, inspired by mussel's powerful wet adhesion in a salted marine environment to diverse interfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…At 1480 cm −1 , both Q-CS and GQ-CS had a larger absorption peak than that chitosan, which can be attributed to the bending vibration of C–H in –N + (CH 3 ) 3 . 35 Differently, GQ-CS had an extra absorption peak to those of chitosan and Q-CS at 1550 cm −1 , which can be attributed to the absorption peak caused by the in-plane bending of N–H on the amide bond formed by CS and GA. At 1595 cm −1 , CS showed a relatively obvious absorption peak, while the Q-CS peak decreased, and the GQ-CS peak was the least, because –NH 2 on chitosan changed from a primary amino to secondary amino. 34 The nuclear magnetic spectrum further proved the successful preparation of GQ-CS.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…At 1480 cm −1 , both Q-CS and GQ-CS had a larger absorption peak than that chitosan, which can be attributed to the bending vibration of C–H in –N + (CH 3 ) 3 . 35 Differently, GQ-CS had an extra absorption peak to those of chitosan and Q-CS at 1550 cm −1 , which can be attributed to the absorption peak caused by the in-plane bending of N–H on the amide bond formed by CS and GA. At 1595 cm −1 , CS showed a relatively obvious absorption peak, while the Q-CS peak decreased, and the GQ-CS peak was the least, because –NH 2 on chitosan changed from a primary amino to secondary amino. 34 The nuclear magnetic spectrum further proved the successful preparation of GQ-CS.…”
Section: Resultsmentioning
confidence: 94%
“…According to previous work, 35 glycidyl trimethyl ammonium chloride (GTMAC) was introduced into the amino group of the chitosan skeleton to obtain quaternized chitosan (Q-CS). Then, 5 g of chitosan was added to 200 mL of deionized water, 1 mL of acetic acid was added to dissolve the CS.…”
Section: Methodsmentioning
confidence: 99%
“…51 The polymerization of catechol groups and catechol into polycatechol is essential for both interfacial adhesion and cohesion. 52 Ban et al 53 developed a chitosan flocculant (CQ-CS) based on mussels, where catechol and cationic trimethylammonium groups were simultaneously grafted onto a chitosan backbone. This flocculant demonstrated high salt tolerance and exhibited excellent performance in flocculating soluble organic dyes and suspended particles in wastewater.…”
Section: Mechanism Of Interaction Of Catechol-based Substancesmentioning
confidence: 99%
“…Flocculation exhibits remarkable advantages in the treatment of large-scale wastewater due to its simplicity, cost-effectiveness, and applicability to both dissolved and insoluble pollutants. However, recent research has shown that commonly used flocculants such as inorganic flocculants like polyaluminum chloride and synthetic organic flocculants like polyacrylamide are toxic to human beings and the environment and have become a new source of secondary pollution due to leakage of metal ions and unreacted monomer residues during flocculant preparation and application. In contrast, natural biopolymer-derived flocculants such as chitosan (CS) offer an excellent solution to the aforementioned toxicity problem. CS is one of the most abundant natural polymers with the advantages of environmentally friendliness, biodegradability, and high performance, and it has been widely explored for treating a wide variety of stimulated and real wastewater. It possesses abundant amino and hydroxyl functional groups on its backbones, allowing it to be modified by various chemical reactions such as amidation, carboxymethylation, and quaternization. , Du et al fabricated a quaternized CS (QCS)-based aerogel with outstanding adsorption capacities, wide versatility, and excellent recyclability for organic dyes. Liu et al successfully prepared a modified CS flocculant, CTS-DAC-AMPS, by introducing acryloyloxyethyl trimethylammonium chloride and 2-acrylamido-2-methylpropanesulfonic acid into the amino group of CS, which was superior to that of the commercially available flocculants in the treatment of industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, QCS flocculants adopt a highly compact configuration with a lower hydration level in saline solutions and thus greatly reduce effective interactions between active sites of flocculant chains and pollutants. , Therefore, to achieve good pollutant removal performance for high-salinity colored effluents, it is of great importance to develop a viable strategy that endows the prepared QCS-based flocculant with enhanced hydration in aqueous solution to provide abundant active sites to interact with more pollutant species. Recently, hydrogen-bond (H-bond) has been emerging as an effective strategy to enhance the hydration of QCS-derived flocculants. , By incorporating extra hydroxyl groups into QCS chains, the obtained QCS flocculant exhibited enhanced H-bond hydration behavior to resist the salting-out effect in saline solution and demonstrated promising flocculation performance to saline colored effluents. , Our previous research indicated that introducing catechol groups into QCS could exert the prepared catechol-grafted flocculant with multiple intermolecular interactions to efficiently treat suspended particles and refractory soluble organic pollutants in saline solution. However, most of these developed QCS flocculants were prepared by modifying reactive amino and hydroxyl functional groups on the CS skeleton and demanded delicate but troublesome tuning of the hydration ability and charge density to achieve good flocculation performance.…”
Section: Introductionmentioning
confidence: 99%